2018
DOI: 10.1136/bmjopen-2017-020841
|View full text |Cite
|
Sign up to set email alerts
|

PRactice of VENTilation in Middle-Income Countries (PRoVENT-iMIC): rationale and protocol for a prospective international multicentre observational study in intensive care units in Asia

Abstract: IntroductionCurrent evidence on epidemiology and outcomes of invasively mechanically ventilated intensive care unit (ICU) patients is predominantly gathered in resource-rich settings. Patient casemix and patterns of critical illnesses, and probably also ventilation practices are likely to be different in resource-limited settings. We aim to investigate the epidemiological characteristics, ventilation practices and clinical outcomes of patients receiving mechanical ventilation in ICUs in Asia.Methods and analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…The digital intensive care unit (ICU) platform has increased availability of variables for benchmarking acuity of admissions and supported the validation of prognostic models 11 19 20 25. The platform has also facilitated participation in international multisite observational studies on ventilation management 26. Prior studies attempting to answer similar questions in this setting have highlighted challenges of lack of information, missing outcomes and small data sets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The digital intensive care unit (ICU) platform has increased availability of variables for benchmarking acuity of admissions and supported the validation of prognostic models 11 19 20 25. The platform has also facilitated participation in international multisite observational studies on ventilation management 26. Prior studies attempting to answer similar questions in this setting have highlighted challenges of lack of information, missing outcomes and small data sets.…”
Section: Discussionmentioning
confidence: 99%
“…In the acute care setting, the adapted mobile version of the digital platform has empowered nurses and doctors to adopt digital vital sign reporting (500 000 observations) in busy ward settings 28. Adaptation of an early warning score has helped identify over 4800 deteriorating ward patients by flagging patients who have deranged physiology on admission, for whom increased frequency of vital signs monitoring may be beneficial 26–28…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately half of patients with ARDS in LUNG SAFE [22] and patients without ARDS in PRoVENT [23] received lung protective ventilation with a low V T and PEEP. While awaiting a detailed report on PRoVENT-iMiC [14], it can already be concluded that lung protective ventilation is also used in ICUs where resources are low.…”
Section: Take-home Messagesmentioning
confidence: 99%
“…A worldwide perspective of ventilator management Marcus Schultz summarised the findings of three recent large service reviews of ventilator management in intensive care unit (ICU) patients: 1) the "Large Observational Study to Understand the Global Impact of Severe Acute Respiratory Failure" (LUNG SAFE) [12]; 2) the "PRactice of VENTilation in patients without ARDS" (PRoVENT) study [13]; and 3) the recently finished "PRactice of VENTilation in Middle-income Countries" (PRoVENT-iMiC) study [14].…”
mentioning
confidence: 99%